Exciplex Formation and Aggregation Induced Emission in Di‐(N‐benzyl)cyclen and Its Complexes – Selective Fluorescence with Lead(II), and as the Cadmium(II) Complex, with the Chloride Ion. Issue 33 (22nd August 2018) - Correia, Bruna B.; Brown, Thomas R.; Reibenspies, Joseph H.; Lee, Hee‐Seung; Hancock, Robert D.
Abstract : DB‐cyclen [1, 7‐bis(phenylmethyl)‐1, 4, 7, 10‐tetraazacyclododecane] was investigated in 50 % CH3 OH/H2 O (v/v) as a fluorescent sensor for heavy metal ions, and as the Cd II complex as a sensor for anions. The Pb II complex showed a unique strong emission at 447 nm, possibly a charge‐transfer band involving the 6p←6s 2 transition of Pb II and the benzyl fluorophore. Zn II uniquely produced a significant emission at 353 nm, suggested to be due to an aggregation induced (AIE) mechanism, possibly involving exciplex formation. The free DB‐cyclen ligand produces a fluorescence band at 354 nm above pH ca. 9, accompanied by the slow formation of an aggregate in suspension as indicated by the presence of light scattering peaks in the absorbance spectra, an AIE effect, due to formation of an intermolecular exciplex in the solid state. The role of M··· C π contacts in quenching fluorescence in DB‐cyclen complexes or in AIE effects was investigated in the structures of [Pb(DB‐cyclen)(ClO4 )2 ] (1 ), [Cu(DB‐cyclen)(ClO4 )2 ] (2 ), [Ag(DB‐cyclen)(ClO4 )] (3 ), and [Cd(DB‐cyclen)(ClO4 )(H2 O)]ClO4 (4 ). In1 there is an intermolecular π contact between the Pb II and a benzyl group from an adjacent complex individual, which is also the case in3, where very short η 2 intermolecular Ag··· C π contacts are found. A strong band at 336 nm is shown in the Cd II DB‐cyclen complex on titration with Cl – only: Br –, I –, S2 O3 2–, and SCN – produced no AIE/exciplex band in the Cd II DB‐cyclen complex: the exciplex forming species may be a Cl – bridged dimer [Cd(DB‐cyclen)Cl]2 2+ . Abstract : DB‐cyclen (1, 7‐dibenzylcyclen) shows a band at 354 nm above pH 9, interpreted as an exciplex emission accompanying aggregate formation. Only the Pb II complex shows an intense emission at 447 nm, which may be a charge‐transfer band involving the 6s 2 →6sp transition. The Cd II DB‐cyclen complex produces a strong exciplex emission only on titration with Cl – ion, suggesting use as an anion sensor.